Evaluation of various plant species for biodiesel production - Ingole, S P; Kakde, A U (Current Botany, 2012)
Fuels are the combustible substances containing carbon, hydrogen as the main constituents. The biomass consists of these carbonaceous materials as the chemical form. In this recent new era when we are facing short listing of conventional fuels, a substitute is urging. Newer inventions and research works are being carried out by various agencies. The biofuel concept is found much helpful, sustainable and environmental friendly. Some members of Euphorbiaceae, some algal species, sugarcane, residues and sugar beet are remarkable in this field. Biomass has been used for energy purposes ever since man discovered fire. With the evolutionary trend man discovered the conventional fuels and started its consumption. The over consumption of these fuels have brought up to the condition that today these fuels are depleted and stocks towards end. To cope up with these conditions, a newer technological concept is to develop the fuels, which are never ending. This need can be fulfilled by the use of non-conventional fuels or resources. Biomass is likely to remain as an important global source in developing countries well in the next century. Some species of petro plants have been found fruitful and a bless in the route. A powerful option for improving our environment while reducing dependence on foreign fuels, and the stretching fossil fuel reserves in the biodiesel. Biodiesel is a clean burning fuel for diesel engines made from domestically produced, renewable fats and oils such as Soybean oil, Jatropha, Pongamia pinnata, and various other species. The aim and purpose of developing these plant species is to incorporate such species, which are economical, beneficial and having potency to grow even in the drastic conditions. India is a country of vast diversity, blessed with all types of vegetation: tropical, subtropical, temperate and alpine. Keeping in mind its economic and development status, some species like Pongamia pinnata, Jatropa curcas, Shorea robusta, Madhuca indica, Pongamia glabra, Azadirachta indica, Magnifera indica, Salvadora oleoides, some grasses like Andropogon, Cymbopogan, Lemon grasses, etc. The oil extracted from these species particularly the Jatropa and Pongamia pinnata has environmental as well as economical benefits. These species are found growing, luxuriantly even in the desertified, barren and waste lands. The oil obtained from the species can be used for lightening lamps, electrification and as a biodiesel for automobiles. Maintenance cost and cost of production are negligible. As expensive can help in employment for locals and increasing soil fertility and green patches of these can be developed for substance of good, healthier environment.